Persinggungan Hukum Pidana dan Perlindungan serta Keharmonisan Keluarga dalam Kriminalisasi Perilaku menurut KUHP Baru - Azka Syifaul Maula (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the intersection of criminal law and the protection and harmony of the family within the context of behavioral criminalization under the new Indonesian Criminal Code (KUHP Baru). Using a normative-juridical approach, the research analyzes statutory provisions, particularly Articles 34 and 43 concerning self-defense and excess defense (noodweer excess), alongside doctrinal and comparative legal literature. The study highlights the tension between legal formalism and social realities, emphasizing that defensive acts aimed at protecting family members, even with fatal consequences, can possess legal legitimacy if proportionality, psychological pressure, and familial obligations are considered. Findings indicate that a contextual, teleological, and systemic interpretation is essential to align criminal law enforcement with family protection and social morality. The research contributes theoretically by clarifying the legal boundaries of self-defense in familial contexts and methodologically by proposing an integrative analytical framework for balancing criminal liability with family harmony.